2018
DOI: 10.3389/fmolb.2018.00036
|View full text |Cite
|
Sign up to set email alerts
|

Drug Interactions With the Ca2+-ATPase From Sarco(Endo)Plasmic Reticulum (SERCA)

Abstract: The sarco(endo)plasmic reticulum Ca2+-ATPase (SERCA) is an intracellular membrane transporter that utilizes the free energy provided by ATP hydrolysis for active transport of Ca2+ ions from the cytoplasm to the lumen of sarco(endo)plasmic reticulum. SERCA plays a fundamental role for cell calcium homeostasis and signaling in muscle cells and also in cells of other tissues. Because of its prominent role in many physiological processes, SERCA dysfunction is associated to diseases displaying various degrees of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 68 publications
0
35
0
Order By: Relevance
“…It has been shown that drug/protein interactions can be conveniently monitored on SSMs. In particular, the SSM technique has demonstrated its usefulness to investigate the effects of various pharmaceutically relevant compounds on P-type ATPases [ 29 , 33 , 111 ], which are important targets for a variety of drugs [ 112 , 113 , 114 ]. Therefore, this technique represents a robust and reliable assay in drug development and evaluation studies on membrane transport proteins, as it can be used to quantify the effectiveness and potency of drugs directed toward specific protein targets, and to characterize novel drug candidates.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that drug/protein interactions can be conveniently monitored on SSMs. In particular, the SSM technique has demonstrated its usefulness to investigate the effects of various pharmaceutically relevant compounds on P-type ATPases [ 29 , 33 , 111 ], which are important targets for a variety of drugs [ 112 , 113 , 114 ]. Therefore, this technique represents a robust and reliable assay in drug development and evaluation studies on membrane transport proteins, as it can be used to quantify the effectiveness and potency of drugs directed toward specific protein targets, and to characterize novel drug candidates.…”
Section: Discussionmentioning
confidence: 99%
“…CPA and DBHQ are less potent compared to thapsigargin; in fact, CPA inhibits SERCA1 with a K i is 120 nM while DBHQ with a K i of 0,4 μM [ 50 ]. Because of their poor pharmacokinetic properties and lack of potency, DBHQ and CPA had a limited application in tumor models, with only few studies exploring the feasibility of their application as anticancer or antimalarial compounds [ 40 , 50 , 147 151 ]. However, similarly to thapsigargin, CPA induces a NOTCH1 off transcriptional program and triggers a NOTCH1 trafficking defect, suggesting that a thapsigargin-like binding mode of action is not an absolute requirement to achieve the suppression of the Notch1 signaling [ 35 ].…”
Section: Cyclopiazonic Acid and 25-di-(tert-butyl)-14-benzohydroquimentioning
confidence: 99%
“…The SERCA pump consists of a single polypeptide chain folded into four major domains: a transmembrane region (M) consisting of 10 helical segments (TM1 to TM10, which include two Ca 2+ -binding sites), and three cytosolic domains named A (actuator), N (nucleotide-binding), and P (phosphorylation). The active transport carried by SERCA can be described by a model termed E1-E2, which is based on a cycle that relies on a change in affinity for Ca 2+ -binding sites (from high-E1 to low-E2), and includes: phosphorylation by ATP, dephosphorylation, and reorientation of Ca 2+ binding sites towards the SR lumen [124,125].…”
Section: Sercamentioning
confidence: 99%